Pengaruh Stres Kerja, Motivasi Kerja, dan Work-Life Balance terhadap Kepuasan Kerja (Studi pada Mahasiswa Manajemen yang Bekerja sambil Kuliah di Universitas Bhayangkara Jakarta Raya) - Mayang Puspita Ayu; Yayan Hendayana; Sri Wulandari (Indo Publishing, 2026)
This study aims to determine the effect of job stress, work motivation, and work-life balance on job satisfaction among Management students who work while studying at Universitas Bhayangkara Jakarta Raya. This research is motivated by the phenomenon of students who take on dual roles as workers and students, making them susceptible to work pressure and difficulties balancing personal life and work, which potentially affects their level of job satisfaction. This study employs a quantitative method with a causal-associative research design. Primary data were obtained through an online questionnaire distributed to 100 respondents selected using purposive sampling, namely Management students at Universitas Bhayangkara Jakarta Raya who work while studying. Data were analyzed using the Structural Equation Modeling-Partial Least Square (SEM-PLS) method with the assistance of SmartPLS 4. The results show that job stress has a positive and significant effect on job satisfaction. Work motivation also has a positive and significant effect on job satisfaction, as does work-life balance. Thus, the three independent variables job stress, work motivation, and work-life balance are proven to have a positive and significant effect on the job satisfaction of Management students who work while studying at Universitas Bhayangkara Jakarta Raya.